Learn Math Questions

from a handpicked tutor in LIVE 1-to-1 classes

from a handpicked tutor in LIVE 1-to-1 classes

# Given: f(x) = x - 7 and h(x) = 2x + 3. Write the rule for h(f(x)).

**Solution:**

Given, f(x) = x - 7

h(x) = 2x + 3

We have to find h(f(x))

h(f(x)) = h(x - 7)

= 2(x - 7) + 3

= 2x - 14 + 3

= 2x - 11

Therefore, h(f(x)) = 2x - 11

Example: **Given: f(x) = 2x - 3 and h(x) = x + 3. Write the rule for h(f(x)).**

**Solution:**

Given, f(x) = 2x - 3

h(x) = x + 3

We have to find h(f(x))

h(f(x)) = h(2x - 3)

= (2x - 3) + 3

= 2x - 3 + 3

= 2x - 0

= 2x

Therefore, h(f(x)) = 2x

## Given: f(x) = x - 7 and h(x) = 2x + 3. Write the rule for h(f(x)).

**Summary:**

Given: f(x) = x - 7 and h(x) = 2x + 3. The rule for h(f(X)) = 2x - 11.

Math worksheets and

visual curriculum

visual curriculum